Fatigue crack propagation test and numerical simulation analysis of B780CF steel - Gu, Lichun; Li, Mingfei; Zhang, Tianhui; Li, Guirong (Frontiers in Materials, 2025)
IntroductionThis is study investigates fatigue crack propagation in B780CF steel, aiming to establish an integrated experimental-simulation analysis framework.MethodsThe fatigue crack growth tests were conducted on compact tensile (CT) specimens under a stress ratio of R = 0.1, the fatigue crack growth rate (FCGR) was calculated using a seven-point polynomial method, and the Paris formula parameters were fitted to the range of stress intensity factors (ΔK). Then, A numerical simulation of fatigue crack propagation based on the J-integral was conducted using an improved meshing strategy.ResultsComparative analysis revealed a 4.9% mean absolute error in fatigue life prediction using the improved meshing approach.DiscussionThis error margin validates the simulation accuracy, demonstrating the framework’s effectiveness in evaluating fatigue crack growth characteristics of B780CF steel.